The predictive value of T-cell chimerism for disease relapse after allogeneic hematopoietic stem cell transplantation - Li, Zhipeng; Wang, Jing; Deng, Lei; Liu, Ximin; Kong, Fanjun; Zhao, Yuerong; Hou, Yixi; Zhou, Fang (Frontiers in Immunology, 2024)
To investigate the predictive value of distinct chimerism for relapse, we measured bone marrow (BM), peripheral blood (PB), and T-cell (isolated from BM) chimerism in 178 patients after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Receiver operating characteristic (ROC) curve showed that T-cell chimerism was more suitable to predict relapse after allo-HSCT compared with PB and BM chimerism. The cut-off value of T-cell chimerism for predicting relapse was 99.45%. Leukemia and myelodysplastic syndrome (MDS) relapse patients’s T-cell chimerism was a gradual decline from 2 months to 9 months after allo-HSCT. Higher risk of relapse and death within 1 year after allo-HSCT. The T-cell chimerism rates in remission and relapse patients were 99.43% and 94.28% at 3 months after allo-HSCT (P=0.009), 99.31% and 95.27% at 6 months after allo-HSCT (P=0.013), and 99.26% and 91.32% at 9 months after allo-HSCT (P=0.024), respectively. There was a significant difference (P=0.036) for T-cell chimerism between early relapse (relapse within 9 months after allo-HSCT) and late relapse (relapse after 9 months after allo-HSCT) at 2 months after allo-HSCT. Every 1% increase in T-cell chimerism, the hazard ratio for disease relapse was 0.967 (95%CI: 0.948-0.987, P＜0.001). We recommend constant monitoring T-cell chimerism at 2, 3, 6, and 9 months after allo-HSCT to predict relapse.